Comparison of Two Techniques of Mandible Fracture Fixation Regarding Their Postoperative Complications (Medical Forum Monthly, 2024)
Objective: The objective of our study was to compare complications of fracture mandible treated by miniplate only and miniplate plus maxilla mandibular fixation (MMF).Study Design: Comparative StudyPlace and Duration of Study: This study was conducted at Liaquat University Hospital Hyderabad from May 2007 to April 2008.Patients and Methods: This study was conducted on (100) one hundred patients of single mandible fracture. Patients were distributed into two groups (Group A and Group B). Patients in group A fracture, fixation was done by miniplate fixation and patients in group B were managed by miniplate plus MMF for upto 15 days. All patients were followed after surgery for at least two months. Incidence of development of infection, nonunion, malocclusion, nerve damage, TMJ dysfunction and delayed union was evaluated.Results: Bone union was occurred in all patients. Ten complications were developed in ten patients. In group A number of complications were 8 (16%) and in Group B number of complications were 2 (4%).Conclusion: Rigid internal fixation in the form of miniplate plus MMF for shorter duration is advantageous as it has good function result and lesser number of compactions.